Implementing multiple strategies to foster reading comprehension in teaching English - Sultonova Munojat Yunusovna (Zien Journals, 2022)
Reading skill is considered as a receptive skill which plays the main role for developing the other skills included writing, speaking and listening. However, majority English teachers and learners find teaching and learning reading quiet boring or challenging. That is why; teachers are recognized the state-of-art reading ways to teach in the classroom. This paper will discuss about powerful strategies for involving learners in developing reading skill and fluency that support reading comprehension, fluency, writing, grammar and vocabulary
Keywords: Reading; receptive skill; boring; challenging